Trials of Antigone and Jesus - Robert, William 1974- (New York Fordham University Press, 2010)
Impossible love -- Between nature and culture -- Surviving, forever foreign -- Cryptic crossing -- Touching transcendence, in the flesh -- The tragedy of Christianity
Includes bibliographical references (p. ) and index
Keywords: Jesus Christ -- Person and offices; Theological Anthropology -- Christianity; Tragic, The -- Religious aspects -- Christianity; Antigone (Greek mythology); Philosophical Anthropology; Tragic, The; Deconstruction; Continental Philosophy